Synchronous and asynchronous online learning in university English language classrooms: findings from Indonesia - Rido, Akhyar; Kuswoyo, Heri; Mandasari, Berlinda; Prakoso, Bagus Hary; Purba, Mariati; Siswanto, Heni Waluyo (Institute of Advanced Engineering and Science, 2024)
English has a significant role in the education and economic sectors. However, learning English has been challenging for students, especially when the implementation of online learning has significantly increased. This research aimed to reveal the reality of English online learning in an Indonesian university, focusing on synchronous and asynchronous technological applications used and challenges faced by students. By employing a qualitative approach, data were collected by observing five English language skills subjects as well as interviewing thirteen volunteered students. The findings revealed that Zoom and Google Meet were used in synchronous online English language classrooms mainly for lectures, discussions, and presentations. Meanwhile, Spada, the university YouTube channel, and the university online portal were used asynchronously for assignments, projects, information updates, peer corrections, forums, and learning materials. Some challenges in synchronous online learning included unstable internet connection, expensive internet data, incompatible gadgets, and low self-confidence. Meanwhile, in asynchronous online learning, some challenges included difficulties in comprehending learning materials, overloaded assignments, and lack of personal time commitment. This research suggested teachers and relevant stakeholders incorporate balanced synchronous and asynchronous online learning in their English language classrooms, improve infrastructure and technology for online learning, and prepare students for the challenges of tomorrow.